Note on the geology of the western part of the Soer Rondane Mountains, East Antarctica - Kojima, Satoru; Shiraishi, Kazuyuki (1986)
P(論文) Results of the geological investigation by the 26th Japanese Antarctic Research Expedition in the western part of the Sor Rondane Mountains are outlined. The area is underlain by various kinds of metamorphic and plutonic rocks. Foliation of gneisses trends E-W, dipping monoclinally southward. The metamorphic rocks are divided into two groups : the northern group which consists of pelitic, psammitic and intermediate gneisses and subordinate amounts of basic and calcareous rocks, and the southern group which comprises gneissose tonalite with basic fragments and minor amounts of pelitic and calcareous gneisses. A pronounced shear zone separates the two groups. Although metamorphic grade of the regional metamorphism reaches up to the granulite facies in the northern group, mineral assemblages showing the epidote-amphibolite facies are commonly observed in the southern part of the northern group and in the southern group. It is characteristic that intense mylonitization associated with retrograde metamorphism under the greenschist facies condition is widespread, especially in the southern group. Plutonic rocks are granite, syenite and diorite which form sporadic stocks and small masses throughout the region. Slightly metamorphosed dolerite dikes which show distinct chilled margins intrude the metamorphic rocks. Newly obtained whole-rock K-Ar age on the dolerite indicates 536±27Ma. departmental bulletin paper